Developing Mathematics Learning Media Using the Sparkol VideoScribe Application in Grade IV Elementary School at State Elementary School 137 Palembang - Nia Elvi Susanti; Misdalina; Tanzimah (Edumaspul: Jurnal Pendidikan, 2026)
This research aims to produce a mathematics learning media using the Sparkol Videoscribe application in class IV at SD Negeri 137 Palembang, which is valid and practical, this research is a development research using the ADDIE (Analysis, Design, Development, Implementation, And Evaluation) model. The research subject is a student of class IV of SD Negeri 137 Palembang. Data collection techniques are carried out by using observation, questionnaires (serraises) and documentation. The research results show that the validity of learning media using the Sparkol Videoscribe application which is developed based on the validation results of expert/expert assessment in terms of: media, material, and language obtained a percentage of 95.43% with the category "Very Valid" based on the questionnaire data. For media practicality obtained from the student response questionnaire assessment, a percentage of 92.66% was obtained with the category of "Very Practical". Based on the validation results by experts/experts and the results of practicality trials, it can be concluded that the learning media using the Sparkol Videoscribe application is suitable for use in the learning process.